Pengaruh Motivasi dan Stres Kerja terhadap Kinerja Karyawan PT “X” Express di Karawang - Rofiqi, Munif; Jamaludin, Asep; Apriani, Zenita (Lembaga Yasin AlSys, 2026)
The development of the delivery service industry in an era of increasingly intense competition requires companies to maintain and improve employee performance, particularly couriers as the frontline of service delivery. This study aims to determine and analyze the effect of work motivation and work stress on employee performance at PT “X” Express in Karawang, both partially and simultaneously. This study used a quantitative approach with a correlational design. The research population included all employees of PT “X” Express in Karawang, with a sample of 100 respondents determined through purposive sampling. Data were collected through questionnaire distribution using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS. The results show that work motivation has a positive and significant effect on employee performance, with a significance value of 0.000 < 0.05 and a regression coefficient of 1.749. Conversely, work stress has a negative and significant effect on employee performance, with a significance value of 0.000 < 0.05 and a regression coefficient of -0.384. Simultaneously, work motivation and work stress have a significant effect on employee performance, with a significance value of 0.000 < 0.05 and a calculated F value of 103.368. The coefficient of determination (R Square) value of 0.681 indicates that 68.1% of the variation in employee performance can be explained by work motivation and work stress, while the remainder is influenced by other variables outside this study. These findings confirm that increasing work motivation and effectively managing work stress are important factors in improving employee performance at PT “X” Express in Karawang. The implications of this study provide a practical basis for the management of delivery service companies in formulating human resource management strategies oriented toward increasing motivation, controlling work stress, and optimizing employee performance.